2018
DOI: 10.1080/14756366.2018.1543286
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of benzothiazin-4-ones: a possible new class of acetylcholinesterase inhibitors

Abstract: A series of nineteen benzothiazin-4-ones from N-(3-aminopropyl) piperidine, 4-(2-aminoethyl)morpholine or 1-(2-aminoethyl)piperidine, aliphatic or aromatic aldehyde and thiosalicylic acid, were synthesized in good yields by multicomponent one-pot reactions. The solvent was toluene and this efficient procedure afforded the desired heterocycles in 5 h. Identification and characterization were achieved by NMR and GC–MS techniques. In vitro AChE activities of all compounds were evaluated in cerebral cortex and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Other studies have reported that the presence of pyrrolidine heterocycle in the synthesised products showed a potential inhibitory effect of AChE 38 , 39 . In addition, previous research from our research group has demonstrated the synthesis of benzothiazinan-4-one and the potential of some compounds in inhibited the AChE activity from hippocampus and cerebral cortex from rats, demonstrating the importance of this heterocycle in the cholinergic action 27 . Comparing these reports with the study proposed in this paper, I point out that the union of thiazolidin-4-one and thiazinan-4-one with pyrrolidine heterocycle aimed at enhancing AChE inhibition activity, as indeed observed with the results found.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Other studies have reported that the presence of pyrrolidine heterocycle in the synthesised products showed a potential inhibitory effect of AChE 38 , 39 . In addition, previous research from our research group has demonstrated the synthesis of benzothiazinan-4-one and the potential of some compounds in inhibited the AChE activity from hippocampus and cerebral cortex from rats, demonstrating the importance of this heterocycle in the cholinergic action 27 . Comparing these reports with the study proposed in this paper, I point out that the union of thiazolidin-4-one and thiazinan-4-one with pyrrolidine heterocycle aimed at enhancing AChE inhibition activity, as indeed observed with the results found.…”
Section: Discussionmentioning
confidence: 53%
“…also reported that Rattus norvegicus AChEs structures must be very similar to human structure and have properties identical to the active site. Also, although some studies use the isolated form of AChE, the use of crude homogenised from rat’s brain structures, as used in the present work, is widely used and proves to be an important source of AChE for in vitro studies 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to GPx-like activity, most of the compounds were able to catalytically reduce peroxide production, and particularly 42a and 42b exhibited higher activities than ebselen used as reference drug. In the H 2 O 2 -sequestering activity, compounds 42a and 42b showed a similar effect to 41 , suggesting that these organoselenium hybrids could represent interesting innovation in the search for new multifunctional agents for AD treatment [ 84 ].…”
Section: Molecular Hybrids Designed As Prototypes Of Drug Candidates mentioning
confidence: 99%
“…Currently, BTZ compounds were identified as a possible new class of acetylcholinesterase inhibitors for curing the symptoms of Alzheimer's disease (8).…”
Section: Introductionmentioning
confidence: 99%